Fe y razón en la filosofía católica: la propuesta de Alasdair MacIntyre - Orrego Sánchez, Cristóbal (Veritas, 2015)
After a brief recollection of the century long debate about Christian philosophy, the author discusses Alasdair MacIntyre's new proposal to enhance a «Catholic philosophy» in the context of our modern crisis of the relationship between faith and reason. The author shares the diagnosis about our present day situation of research universities and their pragmatic exclusion of philosophy and theology, which, in the best case, are reduced to specialized disciplines with no import for other disciplines, and, in most cases, are just expelled from the realm of scientific research. MacIntyre's dialectical proposal in «Three Rival Versions of Moral Enquiry» and in «God, Philosophy, Universities», and in some other minor works, is critically examined and presented as a new way to engage Catholic and non Catholic thinkers in an open and fruitful confrontation, in stead of our present confinement in closed worlds of falsely scientific research. (English)